Phlebotomine sand flies (Diptera, Psychodidae) in an American tegumentary leishmaniasis transmission area in northern Espírito Santo State, Brazil Fauna de flebotomíneos (Diptera, Psychodidae) em área de transmissão de leishmaniose tegumentar americana no norte do Estado do Espírito Santo, Brasil - Thieres Marassati das Virgens; Claudiney Biral dos Santos; Israel de Souza Pinto; Kleber Silveira da Silva; Fernanda Cristina Leal; Aloísio Falqueto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
American tegumentary leishmaniasis is endemic to the Espírito Santo State, Brazil, where it is widely distributed. The composition of the phlebotomine sand fly fauna in an American tegumentary leishmaniasis focus was determined by monthly sampling, using Shannon light traps in an Atlantic Forest reserve and adjacent habitat that had been modified by human activity. Seasonal fluctuations in numbers of the most abundant species were also monitored from June 2004 to May 2006. Of the 6,176 specimens collected, 47.4% were captured in the forest and 52.6% in the disturbed habitat. Although Lutzomyia davisi (60.8%) predominated in specimens from the forest, those captured near human dwellings consisted almost entirely of Lu. choti (72%) and Lu. intermedia (24.3%). All three species occurred throughout the year. Based on our findings, Lu. intermedia probably acts as the principal domestic Leishmania vector in the study area. A leishmaniose tegumentar americana é endêmica e amplamente distribuída no Estado do Espírito Santo, Brasil. Com o objetivo de avaliar a composição da fauna de flebotomíneos e verificar a flutuação sazonal, foram realizadas capturas mensais com armadilhas Shannon modificadas em reserva florestal de Mata Atlântica (Reserva Biológica de Sooretama) e ambiente antrópico adjacente, no período de junho de 2004 a maio de 2006. Foram capturados 6.176 espécimes, dos quais 47,4% ocorreram no ambiente florestal e 52,6%, no ambiente antrópico. Lutzomyia davisi (60,8%) predominou no ambiente florestal e Lu. choti (72%) seguida de Lu. intermedia (24,3%) predominaram no ambiente antrópico. As três espécies ocorreram ao longo de todo o ano. Os dados indicam que Lu. intermedia provavelmente atue como principal vetor domiciliar de Leishmania na área de estudo.